Асоцијација спринт трчања на краће и дуже стазе до промене смера брзине код ученика полиције - Streetman, Aspen; Paspalj, Darko; Zlojutro, Nemanja; Božić, Danijel; Dawes, J. Jay; Kukić, Filip (NBP. Nauka, bezbednost, policija, 2022)
Background: Law enforcement officers may experience unique physical demands while on duty, including pursuing a suspect on foot, clearing obstacles, rapidly moving between covers, and engaging in physical confrontations with violent offenders. Several different change of direction speed (CODS) assessments are routinely used to simulate these demands. However, the relationship between these assessments has not been fully explored. Thus, this study investigated the association of shorter and longer distance sprint running with CODS performance. Methods: Fifteen police students ran the 20-m sprint test, 300-yard shuttle run, and Illinois Agility Test (IAT). Correlation and regression analyses were used to investigate associations. The effect size analysis provided the magnitude of associations. Results: Correlation analysis determined moderate association between 0-10 m, 10-20 m, and 0-20 m sprint performance with the IAT. The regression analysis determined strong linear association of IAT with sprint 0-10 m (R2 = 0.488, F = 12.385, p = 0.004), sprint 10-20 m (R2 = 0.496, F = 12.775, p = 0.003), sprint 0-20 m (R2 = 0.573, F = 17.468, p = 0.001), and no linear association with the 300-yard shuttle run. Conclusions: The current study found a significant positive association between short sprints and IAT performance, suggesting that linear sprinting speed determines a significant proportion of change of direction speed (CODS) performance. Therefore, police students and officers should include sprint training in their physical fitness routine.